A hardship journey of The UN human rights enforcement bodies: a lesson learned for creating future ASEAN human rights mechanism - , Rachminawati; Mokhtar, Khairil Azmin (2019)
Most core UN human rights treaties have been ratified by many countries including southeast Asian countries. The monitoring mechanism under the UN runs quite well and professional. The UN seems has been successfully achieving their organization’s purpose which is to promote and respect human rights and fundamental freedom. However, little evidence show that the implementation is effective.